Effect of Weight Loss Medications on Hepatic Steatosis and Steatohepatitis: A Systematic Review - Pan, Chelsea S.; Stanley, Takara L. (Frontiers in Endocrinology, 2020)
Nonalcoholic fatty liver disease (NAFLD) is a common comorbidity in individuals with obesity. Although multiple pharmacotherapeutics are in development, currently there are limited strategies specifically targeting NAFLD. This systematic review summarizes the existing literature on hepatic effects of medications used for weight loss. Glucagon-like peptide 1 (GLP-1) agonists are the best-studied in this regard, and evidence consistently demonstrates reduction in liver fat content, sometimes accompanied by improvements in histological features of steatohepatitis and reductions in serum markers of hepatic injury such as alanine aminotransferase (ALT). It remains unclear whether these benefits are independent of the weight loss caused by these agents. Literature is limited regarding effects of orlistat, but a small number of reports suggest that orlistat reduces liver fat content and improves histologic features of NASH, benefits which may also be driven primarily by weight loss. A sizeable body of literature on hepatic effects of metformin yields mixed results, with a probability of modest benefit, but no consistent signal for strong benefit. There are insufficient data on hepatic effects of topiramate, phentermine, naltrexone, buproprion, and lorcaserin. Finally, a few studies to date suggest that sodium-glucose co-transporter-2 (SGLT2) inhibitors may reduce liver fat content and cause modest reductions in ALT, but further study is needed to better characterize these effects. Based on available data, GLP-1 agonists have the strongest evidence base demonstrating beneficial effects on NAFLD, but it is not clear if any weight loss medication has effects of NAFLD superior to those of nutritional modification and exercise alone.